BAKTERI RESISTEN ARSEN (As) PADA ALGA Padina australis DARI PERAIRAN KIMA BAJO - Pratiwi Bone; Desy MH Mantiri; Kurniati Kemer; Robert Bara; Rizald Max Rompas; Reiny Tumbol (Sam Ratulangi University, 2021)
Padina australis is a species of marine algae from the Phaeophyta division (brown algae) which is generally distributed in marine waters. This algae is able to live in waters with high levels of heavy metals such as in the Kima Bajo waters. This study aims to isolate arsenic (As)-resistant bacteria in P. australis, observe cell shape and bacterial characteristics, and determine bacterial resistance to antibiotics. The method used is conventional bacterial isolation which has been tested on As2O3 compounds. The results obtained were that P. australis contained arsenic resistant bacteria at concentrations of 250 ppm, 500 ppm, and 1000 ppm. The bacteria obtained were Gram positive, in the form of bacilli. These arsenic-resistant bacteria are also resistant to antibiotics such as amoxicillin, cefixime, and doxycycline.Keywords: Padina australis, Arsen (As), Kima Bajo